Effect Of Swill Feeding On The Reproductive Performance Of Large White Yorkshire Pigs - Ramesh, V.; Kumar, V. Ramesh Saravana; Sivakumar, K.; Singh, D. Anandha Prakash; Thiruvenkadan , A.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
An experiment was conducted to find out the effect of swill feeding on reproductive performance of pigs. A total of sixteen Large White Yorkshire weaned female piglets ( 56 days) were selected at random and were divided into two groups consisting of eight piglets in each group and they were subjected to different feeding regimens viz., 100 per cent concentrate (T1 ) and the same was replaced on DM basis with hostel food waste at 50 per cent level (T2). The overall weight gain and average daily gain was significantly (P
Keywords: Feeding regimens; Growth; Reproduction; Pigs